"No princípio era o caos": limites e possibilidades das práticas informais de aprendizagem musical na escola - Alan Caldas Simões (2019)
This work is a qualitative research about informal music learning in school aiming to answer the following research question: How are the attitudes and behaviour of students and teacher throughout the process of applying informal music learning practices in the school? A subsidiary question emerged during the research process: what kind of dilemmas and challenges students and teacher faced in the school context using informal music learning practices? Musical learning practices used by popular musicians and systematized for formal contexts of teaching by Lucy Green (GREEN, 2002, 2008b) were adopted. During the first semester of 2017, I taught 64 classes in the Escola de Educação Básica e Profissional da Universidade Federal de Minas Gerais (CP/UFMG), organized in 2 Grupos de Trabalho Diferenciados (GTD), arranged in 4 groups, composed of 28 students from 12 to 15 years of age. As central procedures of data analysis and discussion I chose the inductive method of qualitative research called Grounded Theory. Through the analysis of data and based on the process of conscientization described by Paulo Freire, a theoretical model was constructed which determines parameters for the analysis of teacher and students' behaviours in informal music learning in school. Such a model describes the dichotomous relationship between authority and authoritarian categories; freedom and licentiousness, inserted in a dynamic process of teacher and student conscientization in the classroom. This model suggests the need to overcome the school habitus, inheritance of Banking Education that permeates the formation of the Brazilian school, to reach the potential state of Critical Musicality. Finally, it is discussed that this theoretical model can help researchers and music teachers interested in the application of informal music learning in school, in the reflection and evaluation of their teaching practices.